Necrotizing Fasciitis of the Chest in a Neonate in Southern Nigeria - Oluwafemi Olasupo Awe; Emeka B. Kesieme; Babatunde Kayode-Adedeji; Quinzy O. Aigbonoga (Case Reports in Pediatrics)
We discuss the successful saving of a male neonate with necrotizing fasciitis of the chest following a hot fomentation of the umbilicus with exposure of the ribs and the pleural space on the right side. He recovered 5 weeks after admission. We stressed the need to recognize necrotizing fasciitis extending from the upper anterior abdominal wall to the chest following hot fomentation of the umbilicus. The need for multidisciplinary cooperation for excellent outcome is very important, that is, neonatologist, medical microbiologist, and plastic and chest surgeons.